Classificaqao de risco no serviço de emergencia: uma análise para além de sua dimensão tecno-assistencial - Ana Augusta Pires Coutinho (2010)
This study presents a classification experience involving the introduction of the Manchester Triage System (MTS) into the Risoleta Tolentino Neves Hospital, in the City of Belo Horizonte, Brazil. As the introduction process is analyzed, it highlights the transformation occurred in the hospital routines through the point of view of institutional actors who actively participated in MTS planning and operation. The following methodological procedures were employed in the analysis: a) field report derived from participant observation and interviews carried out during the first months when the new MTS system was introduced. This method was aimed at spotting the main difficulties, conflicts, and resistance found in the process; b) focal group performed eight months after the MTS introduction, this method involved emergency department teams and hospital administration members directly concerned with the MTS; c) Health care profile related to the hospital emergency department through the analysis of 73,593 reports about patients who used the emergency service within the eight months after the MTS introduction; d) Interviews conducted with medical doctors who worked at the emergency department on a daily basis, and with out of hospital professionals who participated in the formulation of the policy in the State of Minas Gerais, e) documentary survey such as management reports and official documents. The study pointed to the fact that the population plays a highly prominent role to conform the hospital health care model as people take up an active position in regard to the new rules for the access and operation of emergency departments, which leads to a meaningful increase in the number of patients seen. Results show how the MTS implies important as well as new tensions between the main hospital professional bodies physicians and nurses as it interferes with the medical work autonomy, particularly when prioritization and sequence are defined by the nursing professional. Therefore, it works as an institutional device for